DECIDING ON WHAT TO DECIDE - Salvador Barberà; Anke Gerber (International Economic Review, 2021)
We study two-stage collective decision-making procedures where in the first stage, part of the voters decide what issues will be put in the agenda and in the second stage, the whole set of voters decides on the positions to be adopted regarding the issues that are in the agenda. Using a protocol-free equilibrium concept, we show that essentially any set of issues can be obtained as an equilibrium agenda under two salient classes of voting procedures. Moreover, the chair may manipulate a sequential voting rule such that certain issues do not get to the~floor.
Keywords: 330